Poesia em Fotografia: uma leitura intersemiótica de poemas de Manoel de Barros - Silva, Julliana Barra (2022)
The current research focuses on a reflection around Manoel de Barros’ poetic language from the angle of his photographic processes in poems selectes from the book Ensaios Fotográficos (2000). Starting from the theory of intersemiotic translation studied by Julio Plaza and the transcription elaboratd by Haroldo de Campos, we will try to point out the transit between verbal and visual signs that, by hypothesis, we attribute to the poet’s style. We understand in conjunction with Plaza that to translate poetic verbal signs into photographic visual signs is to pass freely and creatively from system to system in a process of infinite semiosis, thus creating another system. Hence, it is here more precisely to start from the poetic volume Ensaios Fotográficos for a proposal of creative translation, of our own authorship, through a laboratory of experimentation in intersemiotic translations. On this path, we will also enter the field of photography and its various types of signs, with emphasis on iconiticy, appealing to authors such as Vilém Flusser, Roland Barrthes, Philippe Dubois, to develop a photographic sign analysis of the experimental exercise of creation and execution of intersemiotic translations